YouTube-Based Materials: Students’ Perception in English Listening Classroom - Rahmatullah Syaripuddin; Roni; Asriadi Rasyid (Journal of Applied Linguistics, 2023)
Half of the students had difficulty mastering their English listening skills because the instructional facilities did not adequately cover the learning process and the media and method were uninteresting. This study aims to find out students’ perceptions toward the use of YouTube applications implemented in teaching English listening. The sample of the study was Biological students of Universitas Muhammadiyah Parepare, Indonesia. The research instrument used was a questionnaire consisting of three indicators. The indicators measured to know the students' perception were the module, video clips, and materials. Microsoft Excel was used to analyze the data and interpreted using a Likert scale. The result showed that the students' positive perception toward the use of the YouTube application was a very good value. The students' distorted perceptions also showed a very good category. In conclusion, youtube-based material was a very good medium for teaching Listening skills. Keywords: YouTube Application, Students’ Perception, English Listening Skill